O envolvimento da governan??a corporativa, sob a ??tica da teoria dos stakeholders, na gest??o e no controle das entidades esportivas - Ribeiro, Henrique C??sar Melo (2014)
Corporate Governance is based on the premise of conflicts of interest (Jensen; Meckling, 1976), influencing the decision-making process of the administration (Mendon??a et al., 2013), contributing to minimize potential informational asymmetries between managers and other stakeholders interested in the results of the company. Most of these studies measures the governance structure and performance in large companies in the market. In contrast, there are just a few studies focusing on sports organizations with a gap in the issue of corporate governance in sports (FERKINS; SHILBURY, 2012). In this regard, understanding how governance mechanisms work in these organizations and how they influence their management and control is necessary (FERKINS; SHILBURY; MCDONALD, 2009; FERKINS; MCDONALD; SHILBURY, 2010). Also it was observed governing mechanisms that are based on complex relationships, known as Collaborative Governance (HUXHAM, 2000; BERTELS; VREDENBURG, 2004; TODEVA, 2010). In this regard, the Theory of Stakeholders (Freeman; Reed, 1983; Friedman; Miles, 2002; Freeman, 1984) was essential to understand how stakeholders engage both in the management and control of sport organizations. Thus, the research question that guided this study is how the corporate governance from the perspective of stakeholders takes place in the management and control of sport organizations? This leads to the goal of the research that is to analyze the involvement of corporate governance from the perspective of stakeholders in the management and control of sport organizations. In order to answer this question, a research methodology based on the method of multiple case study (Yin, 2005) was designed. The sample studied included four Brazilian sport confederations and also four federations, all of them encompassing the following sports: Athletics , Indoor Soccer, Judo, Table Tennis, and Volleyball. To accomplish the goal of the study, 13 interviews were carried out, being six with presidents and seven with managers. Additionally, non-participant observation and document analysis (including statutes and minutes) available in the studied sports organizations sites were performed. Content analysis (Bardin, 2004) was used to describe, categorize and analyze the collected data. Following suggestions from Miles; Huberman (1994), intra-case analysis followed by cross-case analysis were also undertaken in order to generate useful information. One of the main results of this study is that leaders tends to have a common understanding of the meaning of corporate governance. In this regard, it was observed that the principles that guide good governance practices are applied and emphazised in the sports magazine of the studied organizations. Both the principles of transparency and accountability were the most highlighted and it was observed that these principles directly influence both the management and control of these organizations. It was also observed that the relationship of the organizations with their stakeholders are usually quite good, especially with the government, clubs and athletes. Regarding the impact of these stakeholders in corporate governance, it could be identified that the inmates have greater reach than the external ones. Whereas, when the influence of corporate governance on stakeholders is analysed, all respondents stated that there is a positive influence of good governance practices on stakeholders, being this a prominant influence even to the very continuity of the organization. Given the above, it is emphasized that this study sought to better understand the involvement that corporate governance, through its principles, has on the management and control of sports organizations. In this context, it sought to provide greater transparency and understanding of the constructs studied in an attempt to generate, develop, promote, disseminate, socialize and, thus, create research groups on corporate governance in sports, further optimizing this subject that presently has not yet reached its maturity level.